\(=>\frac{x+5-\left(x+3\right)}{y+7-\left(y+5\right)}=\frac{x+5-x-3}{y+7-y-5}=\frac{2}{2}=1\)
=>x+3=y+5
=>x-y=5-3=2
vay x-y=2
tikc to nha
Đúng 0
Bình luận (0)
\(=>\frac{x+5-\left(x+3\right)}{y+7-\left(y+5\right)}=\frac{x+5-x-3}{y+7-y-5}=\frac{2}{2}=1\)
=>x+3=y+5
=>x-y=5-3=2
vay x-y=2
tikc to nha
hiệu x - y biết \(\frac{x+3}{y+5}=\frac{x+5}{y+7}\)
Hiệu x-y biết
\(\frac{x+3}{y+5}=\frac{x+5}{y+7}\)
tìm hiệu x-y biết: \(\frac{x+3}{y+5}=\frac{x+5}{y+7}\)
hiệu x -y biết :
\(\frac{x+3}{y+5}=\frac{x+5}{y+7}\)
hiệu x-y biết \(\frac{x+3}{y+5}=\frac{x+5}{y+7}\)là
Hiệu x - y biết:
\(\frac{x+3}{y+5}=\frac{x+5}{y+7}\)
1) Hiệu x-y biết :\(\frac{X+3}{Y+5}=\frac{X+5}{Y+7}\)
2) Giá trị của X biết : \(\left(\frac{2}{7}\right)^{6x-7}=1\)
hiệu x-y là, nếu\(\frac{x+3}{y+5}=\frac{x+5}{y+7}\)
Hiệu của x-y biết:
\(\frac{x+3}{y+5}\)=\(\frac{x+5}{y+7}\) trả lời nhanh giúp mình nha